Simultaneous Positron Emission Tomography and Molecular Magnetic Resonance Imaging of Cardiopulmonary Fibrosis in a Mouse Model of Left Ventricular Dysfunction - Brianna F. Moon; Iris Y. Zhou; Yingying Ning; Yin‐Ching I. Chen; Mariane Le Fur; Sergey Shuvaev; Eman A. Akam; Hua Ma; Cesar Molinos Solsona; Jonah Weigand‐Whittier; Nicholas Rotile; Lida P. Hariri; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Aging‐associated left ventricular dysfunction promotes cardiopulmonary fibrogenic remodeling, Group 2 pulmonary hypertension (PH), and right ventricular failure. At the time of diagnosis, cardiac function has declined, and cardiopulmonary fibrosis has often developed. Here, we sought to develop a molecular positron emission tomography (PET)–magnetic resonance imaging (MRI) protocol to detect both cardiopulmonary fibrosis and fibrotic disease activity in a left ventricular dysfunction model. Methods and Results Left ventricular dysfunction was induced by transverse aortic constriction (TAC) in 6‐month‐old senescence‐accelerated prone mice, a subset of mice that received sham surgery. Three weeks after surgery, mice underwent simultaneous PET‐MRI at 4.7 T. Collagen‐targeted PET and fibrogenesis magnetic resonance (MR) probes were intravenously administered. PET signal was computed as myocardium‐ or lung‐to‐muscle ratio. Percent signal intensity increase and Δ lung‐to‐muscle ratio were computed from the pre‐/postinjection magnetic resonance images. Elevated allysine in the heart (P=0.02) and lungs (P=0.17) of TAC mice corresponded to an increase in myocardial magnetic resonance imaging percent signal intensity increase (P<0.0001) and Δlung‐to‐muscle ratio (P<0.0001). Hydroxyproline in the heart (P<0.0001) and lungs (P<0.01) were elevated in TAC mice, which corresponded to an increase in heart (myocardium‐to‐muscle ratio, P=0.02) and lung (lung‐to‐muscle ratio, P<0.001) PET measurements. Pressure‐volume loop and echocardiography demonstrated adverse left ventricular remodeling, function, and increased right ventricular systolic pressure in TAC mice. Conclusions Administration of collagen‐targeted PET and allysine‐targeted MR probes led to elevated PET–magnetic resonance imaging signals in the myocardium and lungs of TAC mice. The study demonstrates the potential to detect fibrosis and fibrogenesis in cardiopulmonary disease through a dual molecular PET–magnetic resonance imaging protocol.